2014
DOI: 10.1089/neu.2013.2984
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology and Functional Outcome in Mild Traumatic Brain Injury: Results from the Prospective TRACK-TBI Study

Abstract: Mild Traumatic Brain Injury (mTBI), or concussion, is a major public health concern. There is controversy in the literature regarding the true incidence of postconcussion syndrome (PCS), with the constellation of physical, cognitive, emotional, and sleep symptoms after mTBI. In the current study, we report on the incidence and evolution of PCS symptoms and patient outcomes after mTBI at 3, 6, and 12 months in a large, prospective cohort of mTBI patients. Participants were identified as part of the prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
328
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 443 publications
(347 citation statements)
references
References 28 publications
15
328
2
2
Order By: Relevance
“…2,10 Interestingly, the consult within 24 hours variable was not predictive of outcome, which suggests that those who do not immediately seek health care may still be at risk of ongoing difficulties. As New Zealand has a no-fault compensation injury scheme, compensation, which has previously been identified as a factor linked to outcome after mTBI, was not investigated in this study.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…2,10 Interestingly, the consult within 24 hours variable was not predictive of outcome, which suggests that those who do not immediately seek health care may still be at risk of ongoing difficulties. As New Zealand has a no-fault compensation injury scheme, compensation, which has previously been identified as a factor linked to outcome after mTBI, was not investigated in this study.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Although labelled as 'mild', increasing evidence suggests that the burden of mild TBI (mTBI) may be 'far from mild'. 2 The Diagnostic and Statistical Manual of Mental Disorders (IV) recognises clusters of these symptoms as post-concussion syndrome. 3 Diagnostic criteria include:…”
Section: Traumatic Brain Injury (Tbi) Occurs Whenmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who suffer mTBI have acute cognitive effects, and a significant number of them have persistent symptoms (McMahon et al, 2014).…”
Section: Cognitive Symptoms In Mtbi and Ptsdmentioning
confidence: 99%
“…Sharp and Jenkins [18] insisted that mild TBI is not always a benign condition as its name implies and patients sometimes fail to recover. They proposed that the term "concussion" should be avoided because it has no clear definition and no pathological meaning, therefore, at worst it encourages an apathetic diagnostic approach [18] et al [29] insisted that the term "mild TBI" is a misnomer for patients with severe postconcussion syndrome. Rapp and Curley [30] reported that mild TBI is a category mistake because of the heterogeneity of the clinical population and clinical presentations, the absence of a unitary etiology of post injury deficits, and the complex idiosyncratic time course of the appearance of these deficits in mild TBI.…”
Section: Definition Of Cerebral Concussion Mild Tbi and Traumatic Amentioning
confidence: 99%